Gold(III) Ions Sorption on Amberlite XAD-16 Impregnated with TBP After Leaching Smart Card Chips - Karolina Zinkowska; Zbigniew Hubicki; Grzegorz Wójcik (Molecules)
Owing to the intensive development of electrical and electronic equipment, there is an increasing demand for precious metals, which are often used for its production. Due to their scarce supply, it is important to recover them from secondary sources. A promising way to recover precious metals are impregnated resins. In this research, Amberlite XAD-16 was impregnated with TBP at the weight ratios of 1:2 and 1:3 using the ‘warm impregnation’ method. Studies were carried out on the sorption of Au(III), Pd(II), Pt(IV), and Rh(III) ions from the model chloride solutions as well as the real solution formed after leaching the smart card chips. Only Au(III) ions were efficiently sorbed on the prepared impregnated sorbents. The best results were obtained at 6 M HCl and the sorbent mass: 0.1 g/25 mL. The maximum sorption capacity for the impregnated sorbents was: 147.91 mg/g (ratio 1:2) and 149.66 mg/g (ratio 1:3). Recovery of Au(III) ions from the real leaching solution was: 97.36% and 97.77%, respectively. The Langmuir isotherm was the best-fit model for the experimental results. Thermodynamic studies proved that the investigated sorption process is spontaneous and exothermic. The desorption process can be easily carried out with 1 M HCl/1 M TU.